Drug-coated balloon in the treatment of coronary left main true bifurcation lesion: A patient-level propensity-matched analysis - Pan, Liang; Lu, Wenjie; Han, Zhanying; Pan, Sancong; Wang, Xi; Shan, Yingguang; Peng, Meng; Qin, Xiaofei; Sun, Guoju; Zhang, Peisheng; Dong, Jianzeng; Qiu, Chunguang (Frontiers in Cardiovascular Medicine, 2022)
Aims: An increasing body of evidence suggests that drug-coated balloon (DCB) angioplasty represents a valuable option for revascularization in selected patients with coronary bifurcation disease. However, there remains a paucity of real-world observational evidence on the efficacy of DCB in left main (LM) true bifurcation lesion. We compared clinical and angiographic outcomes of hybrid [DCB + drug-eluting stent (DES)] versus DES-only strategy (provisional stenting or two-stent strategies) in de novo LM true bifurcated lesions. Methods: The primary endpoint was the 2-year composite rate of target lesion failure (TLF): cardiac death, target vessel myocardial infarction (TVMI), or clinically driven target lesion revascularization (CD-TLR). A routine 1-year angiographic follow-up was scheduled. Propensity-score matching was utilized to assemble a cohort of patients with similar baseline characteristics. Results: Among 1077 eligible patients, 199 who received DCB treatment and 398 who were assigned to DES therapy had similar propensity scores and were included in the analysis. TLF within 2 years occurred in 13 patients (7.56%) assigned to DCB group, and 52 patients (14.36%) assigned to DES group (odds ratio: 0.487; 95% confidence interval: 0.258 to 0.922; P = 0.025; Log-rank P = 0.024). Compared with the DES group, the DCB group resulted in a lower rate of CD-TLR (2.91% vs. 9.42%; P = 0.007). Cardiac death, TVMI, all-cause mortality, and stent thrombosis were comparable between both groups. Patients treated with DES-only were associated with a higher late lumen loss (0.42 ± 0.62mm vs. 0.13 ± 0.42mm, P < 0.001) compared with the DCB group at 1 year. In subgroup analysis, the DCB group also presented a lower incidence of TLF, CD-TLR and stent thrombosis both compared to the two-stent strategy and compared to provisional stenting (Ps < 0.05). Conclusions: The 2-year results of PCI utilizing DCB for LM true bifurcation lesions are superior to employing DES alone in terms of safety and effectiveness.